1999
DOI: 10.21836/pem19990618
|View full text |Cite
|
Sign up to set email alerts
|

Oxytocin and plasma containing leukocytes or a combination of both as treatment of postbreeding endometritis in the horse

Abstract: A total of 342 breeding cycles [262 lactating (L), 80 barren (B)] in 237 mares were evaluated. The effect of the following variables on pregnancy (14 and 42 days) was analysed using a general linear model system. Each cycle was randomly assigned to one of the following treatments: untreated control [f1); oxytocin (20 lU, i.v.), admin stered 0 and 12 to 16 h after breeding [f2); intrauterine infusion of leukoc]te enriched plasma (120 ml) 12 to 16 h after breeding (T3); combined treatment of oxytocin (20 lU, j.v… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
2
0

Year Published

2003
2003
2007
2007

Publication Types

Select...
4

Relationship

1
3

Authors

Journals

citations
Cited by 4 publications
(3 citation statements)
references
References 7 publications
1
2
0
Order By: Relevance
“…Data presented in this work showed that the pregnancy rate of maiden mares bred in the 1 st estrus cycle during the breeding season was significantly lower (63.7%) than that of the mares bred in other estrus cycles (80.3%), results similar to those observed previously by Mattos et al (1997 and1999). However, no significant difference (p>0.05) regarding the EL rate was observed between the first and other estrus cycles, being the EL rates in agreement with those found by Ginther (1992).…”
Section: Discussionsupporting
confidence: 91%
“…Data presented in this work showed that the pregnancy rate of maiden mares bred in the 1 st estrus cycle during the breeding season was significantly lower (63.7%) than that of the mares bred in other estrus cycles (80.3%), results similar to those observed previously by Mattos et al (1997 and1999). However, no significant difference (p>0.05) regarding the EL rate was observed between the first and other estrus cycles, being the EL rates in agreement with those found by Ginther (1992).…”
Section: Discussionsupporting
confidence: 91%
“…The intrauterine infusion of freshly isolated autologous PMN as a treatment of equine endometritis is routinely applied in several Stud-farms in Brazil. Mattos et al (1999) could show that the early pregnancy rate per cycle was significantly higher in barren mares treated with plasma containing neutrophils than in mares treated with oxytocin and in control mares. However, this procedure has some practical limitations, especially if many mares have to be treated at the same time.…”
Section: Discussionmentioning
confidence: 92%
“…The use of peripheral blood neutrophils together with autologous plasma, as a post-breeding treatment, resulted in improved fertility in barren mares. In experimentally infected mares, this treatment helped to eliminate bacteria in less time compared with other treatments (Mattos et al, 1999).…”
Section: Introductionmentioning
confidence: 94%